Inhibition of Interleukin-10 Signaling Induces Microbiota-dependent Chronic Colitis in Apolipoprotein E Deficient Mice. Issue 4 (April 2016) - Singh, Vishal; Kumar, Manish; San Yeoh, Beng; Xiao, Xia; Saha, Piu; Kennett, Mary J.; Vijay-Kumar, Matam
Abstract : Background: Apolipoprotein E (ApoE) mediates potent antiinflammatory and immunomodulatory properties in addition to its roles in regulating cholesterol transport and metabolism. However, its role in the intestine, specifically during inflammation, is largely unknown. Methods: Mice (C57BL/6 or ApoE-deficient [ApoE-KO] mice) were administered either single or 4 injections (weekly) of anti-interleukin (IL)-10 receptor monoclonal antibody (1.0 mg/mouse; intraperitoneally) and euthanized 1 week after the last injection. 16S rRNA sequencing was performed in fecal samples to analyze the gut bacterial load and its composition. Microbiota was ablated by administration of broad-spectrum antibiotics in drinking water. IL-10KO mice were cohoused with ApoE-KO mice or their wild-type littermates to monitor the colitogenic potential of gut microbiota harbored in ApoE-KO mice. Results: ApoE-KO mice developed severe colitis upon neutralization of IL-10 signaling as assessed by every parameter analyzed. 16S rRNA sequencing revealed that the ApoE-KO mice display elevated and altered gut microbiota that were accompanied with impaired production of intestinal antimicrobial peptides. Interestingly, microbiota ablation ameliorates colitis development in ApoE-KO mice. Exacerbated and accelerated colitis was observed in IL-10KO mice when cohoused with ApoE-KO mice. Conclusions: Our study highlights a novel interplay between ApoE and IL-10 in maintaining gut homeostasis and that such crosstalk may play a critical role in the pathogenesis of inflammatory bowel disease. Gut sterilization and the cohousing experiment suggest that microbiota play a pivotal role in the development of inflammatory bowel disease in mice lacking ApoE. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 18 February 2016.